Adopsi Teknologi Insect Hotels untuk Meningkatkan Serangga Berguna Sebagai Upaya Pengendalian Penggerek Buah Kopi (PBKo) di Desa Kalibaru Wetan, Banyuwangi - Kurnianto, Agung Sih; Haryadi, Nanang Tri; Dewi, Nilasari; Berliand, Ghalih Daffa; Hanafi, Ahmad Rifqi Alief; Witjakso, Michele Aprilia; Febrianti, Wanda Hamidah Zakiyah; Oktaviani, Nabiila Salsabil; Solekhah, Jihan Lutviatus (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Kalibaru Wetan Village, located in Kalibaru Subdistrict, Banyuwangi Regency, has potential natural wealth and superior agriculture. The agricultural area of Kalibaru Wetan Village covers a total area of 70.75 km². One of the village's primary commodities is coffee. The problems in the coffee plantations of Kalibaru Wetan Village include (1) high population of coffee berry borer (PBKo) pests attacking the coffee plants, (2) excessive use of synthetic pesticides harmful to the environment, and (3) low diversity of beneficial insects in the coffee fields. Based on these issues, it is necessary to disseminate the effects of synthetic pesticide use and the technology of insect hotels to farmers. The purpose of this community service activity is to transfer knowledge to farmers about the harmful effects of synthetic pesticides, the importance of insect diversity, and the use of insect hotel technology. The proposed solution is to implement insect hotel technology. The methods used in this community service activity include insect inventory, socialization, training on making and installing insect hotels, and program monitoring and evaluation. The results of the community service showed an increase in the diversity of insects in the coffee fields, with the number of beneficial insects such as honey bees and black ants increasing from 15 to 45 and from 20 to 60, respectively. Additionally, the use of synthetic pesticides by farmers significantly decreased from 50 liters per month to 15 liters per month. This program also successfully enhanced farmers' knowledge and skills in sustainable and environmentally friendly pest management.